2012
DOI: 10.1016/j.jcgg.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa costovertebral arthritis in association with spontaneous cervical spondylodiscitis and epidural abscesses in the elderly

Abstract: a b s t r a c tCervical spondylodiscitis is an uncommon skeletal infection and its association with Pseudomonas aeruginosa has only been described in isolated case reports. Causes of cervical spondylodiscitis in these patients have been identified, except for the present case. A man aged 78 years with no significant previous medical history presented with an 8-week history of cervical pain and bilateral C5-7 radiculopathy. Magnetic resonance imaging revealed epidural abscesses and the destruction of C7 and T1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In our patient's case, the fact that he had an unusual microorganism ( Pseudomonas aeruginosa ) without any risk factors, that predispose patients to develop such infection (Old age, Immunocompromised status, Diabetes Mellitus, and IV drug abuse) [13] , [14] , and the failure of the first arthroscopic washout and debridement procedure, as well as the ineffective empirical antibiotic regimen that is directed at more commonly involved bacteria [2] , [3] . This all lead to our decision, to use diluted Povidone-Iodine for less than 45-seconds [9] in the second arthroscopic lavage, since it is effective against orthopedic infections, cheap, available, and has no reported adverse effects [15] , followed by copious irrigation with normal saline.…”
Section: Discussionmentioning
confidence: 84%
“…In our patient's case, the fact that he had an unusual microorganism ( Pseudomonas aeruginosa ) without any risk factors, that predispose patients to develop such infection (Old age, Immunocompromised status, Diabetes Mellitus, and IV drug abuse) [13] , [14] , and the failure of the first arthroscopic washout and debridement procedure, as well as the ineffective empirical antibiotic regimen that is directed at more commonly involved bacteria [2] , [3] . This all lead to our decision, to use diluted Povidone-Iodine for less than 45-seconds [9] in the second arthroscopic lavage, since it is effective against orthopedic infections, cheap, available, and has no reported adverse effects [15] , followed by copious irrigation with normal saline.…”
Section: Discussionmentioning
confidence: 84%
“…Vertebral osteomyelitis (spondylodiscitis) is an uncommon condition. It has been reported that the estimated annual incidence is approximately 2.4 cases per 100,000 [1], though other reports indicate a rate as high as 5.4 per 100,000 [2]. The lumbosacral spine is involved most frequently followed by the thoracic then cervical spine.…”
Section: Discussionmentioning
confidence: 99%